The effect of perceived motivation of sports sponsorship: Evidence from basketball fans - Konstantinos Koronios; Marina Psiloutsikou; Athanasios Kriemadis; Petros Kolovos (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The purpose of this study is to single out the key variables in the sport sponsorship relationship, and more specifically to examine the impact of Team Achievement, Sponsor Recognition and Sponsor Altruism on two major behavioural outcomes, fans' purchase intention and word of mouth communication. Design/methodology/approach - A quantitative method was adopted for the scope of this research and questionnaires were collected from fans of a prominent Greek basketball team. A total of 801 questionnaires were collected and interpreted by means of SPSS. Findings - The proposed model was supported by the empirical evidence. All (with the exception of one) research hypotheses were confirmed, either fully or partially (all or some of the distinct dimensions of our independent variables have a significant effect on all or some of the distinct dimensions of the dependent variables). Research limitations/implications -The sample used was predominantly individuals highly involved in the sports club and in basketball in general. As a result, the overall accuracy of the identified sponsors may have been different in case of a different population o sample, not so familiar with these two factors. Furthermore, the fact that the results came from only one type of sport and also from sport fans of a specific club, makes their generalization more sensitive. Originality/value - This research tests an integrated sponsorship model, well known in the respective literature. Nevertheless, the results draw not on the general opinions of fans regarding sponsors but on their opinion about the actual sponsors of the team they support.
Keywords: M3; Z20; 330; Sponsorship; sports; sponsor recognition; purchase intention; word of mouth communication